EVALUATION OF TEACHER PERFORMANCE FROM THE PERSPECTIVE OF ISLAMIC EDUCATION MANAGEMENT - Ulfa Dj. Nurkamiden; Andrianto Mokodompit (LP2M IAIN Sultan Amai Gorontalo, 2024)
This research aims to analyze the teacher performance evaluation system in the context of Islamic education management. Evaluation of teacher performance is an important component in improving the quality of Islamic education. This research examines how the Islamic perspective views teacher performance evaluation and its implementation in Islamic educational institutions. The research method used in this research is a literature review, the data of which is obtained from various relevant literature. The research results show that: First, the concept of teacher performance evaluation in Islam is based on the principles of al-ilah (justice), trust, and continuity which originate from the Al-Quran and Hadith. Second, teacher performance evaluation indicators not only cover professional aspects (pedagogical, social, personality and professional) but also spiritual aspects which include understanding and implementing Islamic values ​​in learning. Third, the implementation of teacher performance evaluation in Islamic education institutions shows an integrative pattern between national competency standards and Islamic values. This research concludes that teacher performance evaluation from an Islamic education management perspective is a comprehensive system that combines aspects of professionalism with Islamic spiritual values, which aims not only to improve the quality of learning but also to build the Islamic character of students.